Pattern of Lipid Profile in Chronic Renal Failure Patient with GFR < 60 ml/min/1.73 m2 on Conservative Treatment Versus Maintenance Haemodialysis (Bangladesh Journal of Medicine, 2016)
The incidence and prevalence of chronic kidney disease (CKD) are increasing worldwide and are associated with poor outcomes. It becomes apparent that the severity of CKD along with CVD severity in any population makes a devastated combination for both patients and healthcare system. Identification of CKD as a major risk factor for cardiovascular morbidity and mortality is attributed to dyslipidemia, and therefore an expectation of effective intervention to diminish premature cardiovascular mortality and progression of renal disease to increase longevity is imperative, thus this study may explore the lipid profile in chronic renal failure patient; on conservative treatment and maintenance haemodailysis treatment. A cross sectional comparative study was carried out to find out the Pattern of lipid profile in chronic renal failure patient with GFR < 60 ml/min on conservative treatment versus maintenance haemodialysis admitted in a selected hospital of Dhaka city. Total 128 study population were selected according to selection criteria among which 62 subjects were on maintenance dialysis (designated as group A) and 66 subjects were on conservative treatment of CKD (designated as group B). On average cholesterol, LDL and triglyceride level were more in group B than group A. On the other hand, HDL level was more in group A than group B and it was statistically insignificant. At the same time average LDL/HDL ratio was higher in group B than group A. But all these differences were statistically insignificant. Among the group A patients average triglyceride, total cholesterol and LDL level were higher in stage 4 CKD patients than stage 5 CKD patients. Average HDL level was higher in stage 5 CKD patients than stage 4 CKD patients. Among the group B patients average triglyceride and LDL level were higher in stage 4 CKD patients. But none of these two differences were statistically significant. On the other hand, average total cholesterol level was higher in stage 3 CKD patients and it was statistically significant(p